2018
DOI: 10.1590/1678-4162-9574
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of rabies in wild animals in the state of Sergipe, Brazil

Abstract: The wild cycle of rabies constitutes a serious challenge to epidemiological surveillance for disease control in domestic, companion or production animals, and in humans. The understanding of rabies virus circulation in the natural environment is increasingly important due to the constancy of natural reservoirs of the disease and the presence of potential vectors of the infection to humans and domestic animals. Aiming to evaluate the occurrence of rabies in the State of Sergipe a total of 935 hematophagous bats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The findings reported here are in agreement with previous studies performed in different biomes in Brazil, which demonstrated that wild animals have been exposed to RABV as indicated by detection of RABV antigens or RVNA identification (Antunes et al, ; Araujo et al, ; Cordeiro et al, ; Jorge et al, ; Rocha et al, ). In Brazil, from 2002 to 2012, the number of laboratorial confirmed cases of rabies, by direct fluorescent antibody test (DFAT) in terrestrial wild animals was 460 (Rocha et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The findings reported here are in agreement with previous studies performed in different biomes in Brazil, which demonstrated that wild animals have been exposed to RABV as indicated by detection of RABV antigens or RVNA identification (Antunes et al, ; Araujo et al, ; Cordeiro et al, ; Jorge et al, ; Rocha et al, ). In Brazil, from 2002 to 2012, the number of laboratorial confirmed cases of rabies, by direct fluorescent antibody test (DFAT) in terrestrial wild animals was 460 (Rocha et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the circulation of RABV in wildlife, and particularly in bats, has now become a major concern for public health (Fisher, Streicker, & Schnell, ; Freire de Carvalho et al, ; Lee et al ,; Rupprecht et al, ).In the last decade, most human deaths in Brazil are attributed to spillover from the vampire bat Desmodus rotundus (Secretaria de Vigilancia em Saude & Ministerio da Saude, ) . Foxes (i.e., crab‐eating fox Cerdocyon tho us) and primates (i.e., marmoset Callithrix jacchus ) have also been identified as reservoirs of RABV variants (Antunes et al, ; Favoretto et al, ; Kotait, De, Maria, & Carrieri, ; Páez, Saad, Núñez, & Bóshell, ) and can transmit rabies to humans (Freire de Carvalho et al, ; Velasco‐villa et al, ). In addition, serological studies have shown evidence of exposure to RABV in the absence of clinical signs in several primates and marsupials species (Antunes et al, ; Araujo et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations